The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.aca.2019.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Competitive electrochemical immunosensor for the detection of unfolded p53 protein in blood as biomarker for Alzheimer’s disease

Abstract: Alzheimer's disease is one of the most common causes of dementia nowadays, and its prevalence increases over time. Because of this, accurate methods for the analysis of specific biomarkers for an early diagnosis of this disease are much needed. Recently, the levels of unfolded isoform of the multifunctional protein p53 in plasma have been proved to increase selectively in Alzheimer's Disease patients in comparison with healthy subjects, thus entering the list of biomarkers that can be used for the diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 46 publications
0
17
0
1
Order By: Relevance
“…Compared to healthy elderly controls, p53 in AD patients exhibited a 100% increase in p53 in the superior temporal gyrus, and induced the phosphorylation of tau in HEK293a cells in vitro [ 728 ]. Dysregulation of p53 such as unfolded p53 caused by oxidative stress [ 780 ] is a reliable biomarker for AD [ 781 , 782 ], whereas overexpression of the truncated p53 isoform p47 (Δ40p53 or p44) [ 783 ] in mice accelerated aging and increased tau fibrillation [ 782 , 784 , 785 ]. Tau was recently reported to have increased wild-type p53 expression post-translationally through the abnormal modification of MDM2, the E3 ubiquitin ligase which negatively regulates p53 [ 786 , 787 , 788 , 789 ].…”
Section: Melatonin May Attenuate the Stress-induced Aggregation Of Pathological Mlos Via Post-translational Modification And Rna Modificamentioning
confidence: 99%
“…Compared to healthy elderly controls, p53 in AD patients exhibited a 100% increase in p53 in the superior temporal gyrus, and induced the phosphorylation of tau in HEK293a cells in vitro [ 728 ]. Dysregulation of p53 such as unfolded p53 caused by oxidative stress [ 780 ] is a reliable biomarker for AD [ 781 , 782 ], whereas overexpression of the truncated p53 isoform p47 (Δ40p53 or p44) [ 783 ] in mice accelerated aging and increased tau fibrillation [ 782 , 784 , 785 ]. Tau was recently reported to have increased wild-type p53 expression post-translationally through the abnormal modification of MDM2, the E3 ubiquitin ligase which negatively regulates p53 [ 786 , 787 , 788 , 789 ].…”
Section: Melatonin May Attenuate the Stress-induced Aggregation Of Pathological Mlos Via Post-translational Modification And Rna Modificamentioning
confidence: 99%
“…The protein p53 responds to cellular stress, and the relationship between conformationally altered p53 and AD diagnosis in blood has been studied since 2008 when Lanni and coauthors observed unfold p53 in peripheral blood cells of AD patients. Recently, unfolded protein p53 was determined from blood in the work of Amor-Gutiérrez and coauthors (2020) using a competitive electrochemical immunosensor with promising results [ 46 , 47 ].…”
Section: Alzheimer's Disease Biomarkersmentioning
confidence: 99%
“…Amor-Gutiérrez et al [ 95 ] developed an immunosensor for the detection of unfolded p53 in blood samples ( Figure 4 A). Using a SPCEs modified with AuNPs for the immobilization of monoclonal antibodies against p53, they developed a competitive biosensor able to detect unfolded p53 by linear sweep voltammetry (LSV), with a LOD of 0.05 nM.…”
Section: Electrochemical Biosensors For Alzheimer’s Disease Diagnomentioning
confidence: 99%
“…( A ) Schematic representation of a competitive immunosensor for the detection of p53 peptide using streptavidin labelled alkaline phosphatase (S-AP) as electrochemical signal (left), accompanied by LSV voltammograms of different p53 concentrations and the corresponding calibration curve (right). Reprinted from [ 95 ]. Copyright (2020) with permission from Elsevier.…”
Section: Figurementioning
confidence: 99%